Vav3-Deficient Astrocytes Enhance the Dendritic Development of Hippocampal Neurons in an Indirect Co-culture System - Wegrzyn, David; Zokol, Josephine; Faissner, Andreas (Frontiers in Cellular Neuroscience, 2022)
Vav proteins belong to the class of guanine nucleotide exchange factors (GEFs) that catalyze the exchange of guanosine diphosphate (GDP) by guanosine triphosphate (GTP) on their target proteins. Here, especially the members of the small GTPase family, Ras homolog family member A (RhoA), Ras-related C3 botulinum toxin substrate 1 (Rac1) and cell division control protein 42 homolog (Cdc42) can be brought into an activated state by the catalytic activity of Vav-GEFs. In the central nervous system (CNS) of rodents Vav3 shows the strongest expression pattern in comparison to Vav2 and Vav1, which is restricted to the hematopoietic system. Several studies revealed an important role of Vav3 for the elongation and branching of neurites. However, little is known about the function of Vav3 for other cell types of the CNS, like astrocytes. Therefore, the following study analyzed the effects of a Vav3 knockout on several astrocytic parameters as well as the influence of Vav3-deficient astrocytes on the dendritic development of cultured neurons. For this purpose, an indirect co-culture system of native hippocampal neurons and Vav3-deficient cortical astrocytes was used. Interestingly, neurons cultured in an indirect contact with Vav3-deficient astrocytes showed a significant increase in the dendritic complexity and length after 12 and 17 days in vitro (DIV). Furthermore, Vav3-deficient astrocytes showed an enhanced regeneration in the scratch wound heal assay as well as an altered profile of released cytokines with a complete lack of CXCL11, reduced levels of IL-6 and an increased release of CCL5. Based on these observations, we suppose that Vav3 plays an important role for the development of dendrites by regulating the expression and the release of neurotrophic factors and cytokines in astrocytes.